The learning factors, shadowing exercises through MALL, and listening ability among Chinese EFL learners - Xiuzhen, Jia; Keat, Ooi Boon (Edelweiss Applied Science and Technology, 2025)
This comprehensive study delves into the multifaceted relationships between various learning factors, the implementation of shadowing exercises through mobile-assisted language learning (MALL), and the enhancement of listening ability among Chinese learners of English as a Foreign Language (EFL). The research was conducted at ten vocational colleges in Wuxi City, China, involving 499 participants who were surveyed. Of these, 406 completed valid questionnaires, providing rich data for analysis. The findings underscore the pivotal roles of school support, the influence of English teachers, the availability and quality of learning facilities, and the intrinsic motivation of learners in shaping listening proficiency. Notably, the integration of shadowing exercises via MALL emerged as a significant mediator, amplifying the positive impacts of these factors on listening ability. This study not only reaffirms the importance of a supportive and resource-rich educational environment but also highlights the transformative potential of technology in language education. The results prompt a reevaluation of current pedagogical strategies and advocate for a more integrated approach to EFL instruction, leveraging both traditional and innovative methods to foster learner success. With implications for educational policy, teacher training, and curriculum development, this research contributes to the ongoing dialogue on optimizing language learning outcomes in a digital age.